Keadilan Restoratif dalam Sistem Peradilan: Memahami Dinamika Bisnis Ilegal Peredaran Gelap Narkotika di Indonesia - Suparja; Arthur Josias Simon Runturambi (Perspektif Hukum, 2024)
This article discusses a concrete legal issue related to drug trafficking in Indonesia, focusing on the challenges of law enforcement and the impact of corruption within the judicial system. Corrupt practices among law enforcement officials hinder the effectiveness of law enforcement and exacerbate drug-related problems. This research reveals that corruption, particularly in the form of bribery, has created an environment conducive to the narcotics trade, resulting in overcrowding in correctional facilities and neglecting rehabilitation for addicts. By analyzing the factors influencing the sustainability of the narcotics business and its impact on society, this article offers recommendations for a more holistic legal approach, including the implementation of restorative justice and more effective alternative sentencing. Through a deeper understanding of the interaction between law and corrupt practices, it is hoped that more effective strategies can be formulated to address the narcotics issue in Indonesia.